Performance of selected woody agroforestry species grown on an Alfisol and an Ultisol in the humid lowland of West Africa, and their effects on on soil properties - Kang, B.; Akinnifesi, F.K.; Ladipo, D.O. (1994)
Performance of commonly grown agroforestry woody species was assessed at two locations in southern Nigeria, on an Alfisol (Oxic Paleustalf) at Ibadan in the forest-savanna transition zone and on an Ultisol (Typic Paleudult) at Onne in the forest zone, with annual rainfall of 1280 and 2400 mm respectively. The improvement effect of the wood species on soil properties appeared to be more pronounced on the Alfisol than on the acidic and nutrient poor Ultisol. Cordia alliodora and Gmelina arborea performed equally well on both sites, but Cardia alliodora seemed to be more suitable for use in an agroforestry system. Leucoma leucocephala and Pterocarpus soyauxii, which performed better on the Alfisol, were more suitable for use in agroforestry systems in this ecozone. Dialium guiñéense, Irvingia gabonensis, and Treculia africana had more potential for use in agroforestry systems on the Ultisol in the humid forest zone. Fruit productivity in these wild fruit species was found to differ between sites; substantial between-tree variations were observed. Indicative productivity values for future economic evaluations of Irvingia gabonensis plantations are presented.